2017
DOI: 10.3389/fpls.2017.00342
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling of Paulownia Seedlings Infected with Phytoplasma

Abstract: Phytoplasma is an insect-transmitted pathogen that causes witches' broom disease in many plants. Paulownia witches' broom is one of the most destructive diseases threatening Paulownia production. The molecular mechanisms associated with this disease have been investigated by transcriptome sequencing, but changes in protein abundance have not been investigated with isobaric tags for relative and absolute quantitation. Previous results have shown that methyl methane sulfonate (MMS) can help Paulownia seedlings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…To reveal the important factors for PaWB occurrence, in our laboratory, we have investigated the transcriptome, DNA methylation, metabolome, and proteome of the three Paulownia species [18,19,[55][56][57]. Most of these researches have indicated that photosynthesis is arrested in PaWBinfected seedlings, which is similar to what was reported in other phytoplasma-infected plants [58,59].…”
Section: A Mir156-mir160-mir5368 Cluster Regulates Leaf Yellowing In mentioning
confidence: 68%
See 2 more Smart Citations
“…To reveal the important factors for PaWB occurrence, in our laboratory, we have investigated the transcriptome, DNA methylation, metabolome, and proteome of the three Paulownia species [18,19,[55][56][57]. Most of these researches have indicated that photosynthesis is arrested in PaWBinfected seedlings, which is similar to what was reported in other phytoplasma-infected plants [58,59].…”
Section: A Mir156-mir160-mir5368 Cluster Regulates Leaf Yellowing In mentioning
confidence: 68%
“…MiRNAs play important roles in hormone medicated morphology development [69]. In our previous proteome and miRNA sequencing studies of paulownia-phytoplasma interactions, we detected changes in gibberellins and brassinosteroids, and abscisic acid biosynthesis in response to phytoplasma infection [23,56]. A previous transcriptome study identified two key cytokinin biosynthesis enzymes that were obviously induced [19].…”
Section: A Mir160-mir172-mir397 Cluster Regulates Leaf Dwarf Morpholomentioning
confidence: 84%
See 1 more Smart Citation
“…From the physiological aspects, we obtained auxin, and amino acids decrease [ 7,8], whereas cystine catalase, auxin oxidase, and vitamin C oxidase increase [ 8,9]. In addition, we identified genes, proteins, and metabolites that responded to phytoplasma infection [10][11][12][13][14][15][16]. However, short-read sequence needs to be assembled into full-length transcripts, which lose a lot of alternative splicing (AS).…”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin treatment can make PaWB-infected Paulownia recover to normal morphology [13]. Furthermore, the rapid development of 'omics' has allowed for the investigation of the transcriptomes [3,[14][15][16][17][18], microRNAs (miRNAs), degradomes [19][20][21][22], and proteomes [4,23] of Paulownia species, and the results have revealed changes after PaWB infection at transcriptional, post-transcriptional, and translational levels.…”
Section: Introductionmentioning
confidence: 99%